Tindak Tutur Deklarasi Bahasa Minangkabau Pedagang Kakilima di Pasaraya Padang - Erlian, Wahyu; Amir, Amril; Noveria, Ena (Universitas Negeri Padang, 2013)
The purpose to the research are described the speech act and to describe the strategy of speech act who use by a pavament seller on transaction in Pasar Raya Padang. The data of the research is speech act that used by the pavemant seller. On the research the writer choose the oral data as the primary source, with direct speech by informan as native speaker. The writer collected data with simak libat cakap methode and technique record. On the research, writer found several problem. First the writer found four kind of declaration of speech act who use by the seller on the transaction; (a) decision speech act, (b) canceled speech act, (c) forbid speech act, (d) permission speech act. Second, there is three strategies that use by seller; (a) the strategy of directspeech act without politeness, (b) the strategy of direct speech act with possitive politeness, (c) the startegy of direch speech act with negative politeness.